Demographic Profile and Adoption of Artificial Intelligence Enabled Banking Services: An Empirical Study of Bank Customers in Coimbatore District (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The banking industry's quick adoption of artificial intelligence (AI) has drastically changed consumer interaction, service delivery, and operational effectiveness. Evaluating the uptake and acceptance of AI-enabled banking services requires an understanding of consumer demographics. This study looks at how certain bank customers in the Coimbatore district use AI banking based on personal criteria. A structured questionnaire was used to gather primary data from 385 respondents, and descriptive statistical methods were used for analysis. The results show that the majority of users of AI-based banking services are young, educated, and salaried consumers, especially those who work in the private sector. consumers with moderate income levels have considerable engagement with AI technologies, whereas female consumers exhibit slightly higher adoption levels than male customers. The study offers insights for banks to improve technology-driven financial inclusion and customer-centric initiatives while highlighting the increasing adoption of AI banking across various demographic categories.